If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + 7 = 5 + -1(8x + 4) Reorder the terms: 7 + -3x = 5 + -1(8x + 4) Reorder the terms: 7 + -3x = 5 + -1(4 + 8x) 7 + -3x = 5 + (4 * -1 + 8x * -1) 7 + -3x = 5 + (-4 + -8x) Combine like terms: 5 + -4 = 1 7 + -3x = 1 + -8x Solving 7 + -3x = 1 + -8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '8x' to each side of the equation. 7 + -3x + 8x = 1 + -8x + 8x Combine like terms: -3x + 8x = 5x 7 + 5x = 1 + -8x + 8x Combine like terms: -8x + 8x = 0 7 + 5x = 1 + 0 7 + 5x = 1 Add '-7' to each side of the equation. 7 + -7 + 5x = 1 + -7 Combine like terms: 7 + -7 = 0 0 + 5x = 1 + -7 5x = 1 + -7 Combine like terms: 1 + -7 = -6 5x = -6 Divide each side by '5'. x = -1.2 Simplifying x = -1.2
| t=225+0.02(325) | | 19n+17=14n-13 | | 3x+62=3x-9 | | t=200+25+.02x | | 5-(6-(3-(7+3)))= | | 4.2+3.9+5+x=21.5 | | X+11=3x+62 | | 25+8k=3(8+3k)-7 | | 5x-13=-27 | | x+11=3x-9 | | -11r-12r=0 | | (4z/11)+(3/11)=-1 | | 8(4x-2)=4(8x+8) | | 33-4(5)+6= | | (4a/5)-(7/5)=(-3/5) | | 8/9+9/-4 | | 2x^2-6x=-5 | | 6x-10=11x-20 | | 1+2b-3b=-4 | | 1c-45=4c+3 | | 33-4n+6forn=5 | | -1/6(x-12)+1/3(x+3)=x-27 | | 8(t+2)-3(t-4)=-3(5y-7)+8 | | 9+11x-7=9x+18-2x | | -2(p-5)+5p=-5 | | 4X+32Y=-16 | | 4+12a=22+6a | | 7a-3x= | | 8(t+2)-3(t-4)=-3(5y-7)-8 | | -1/9(x-27)+1/3(x+3)=x+11 | | y=-5/3x+7 | | 6/3 |